Evaluation of the Effects of Microwave Diathermy in Patients with Chronic Low Back Pain - Hossain, S M Eqbal; Hawlader, Anisur Rahman; Alam, Mohammad Shafiqul; Al Emran, Md; Moslem, Mir Hasan Md; Ahmed, Badrunnesa (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Low back pain is very common in every community. About 60-80% of people suffer from back pain in their whole life. It is tagged as one of the most common causes for absence from work. Microwave diathermy (MWD) is an important treatment modality which is used as an adjunct to other treatment options. In our country, very few studies were carried out in this regard. Objectives: To find out the efficacy of MWD chronic LBP when given with other usual treatment options like various medications and back muscle strengthening exercise. Methods: We evaluated 60 patients suffering from chronic LBP. Those who attended Orthopaedic department, CMH Barishal were divided randomly into two groups and treated with all conventional back pain modalities with or without microwave diathermy. Study design was case control study. It was conducted in CMH Barishal from January 2021 to December 2022. Patients were examined weekly for six weeks. After six weeks, the results were observed and compared. Data were collected by questionnaire and compared by Lattinen test score. Results: Pre-treatment overall score with Lattinen test score system in MWD group was 9.75±4.45 and in non MWD group was 9.5±4.5. After 6 weeks, Group MWD score was 3.20±4.25 whereas Group non MWD score was 5.5±5.6. We found significant improvement of Lattinen test score with application of microwave diathermy after 6 weeks (P<0.05). There was significant improvement in MWD group (P<0.05). Conclusion: This study reveals that MWD can be an effective adjunct to usual treatment modalities. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 50-54